Orthodontic Treatment of a Mandibular Incisor Extraction Case with Invisalign - Khalid H. Zawawi (Case Reports in Dentistry)
Mandibular incisor extraction for orthodontic treatment is considered an unusual treatment option because of the limited number of patients that meet the criteria for such treatment. Accurate diagnosis and treatment planning is essential to achieve the desired results. Adult orthodontic patients are increasingly motivated by esthetic considerations and reject the idea of conventional fixed appliances. In recent years, Invisalign appliances have gained tremendous attention for orthodontic treatment of adult patients to meet their esthetic demands. In this case report, a case of Class I malocclusion was treated with mandibular incisor extraction using the Invisalign appliance system. Successful tooth alignment of both arches was achieved. The use of Invisalign appliance is an effective treatment option in adult patients with Class I malocclusion that requires incisor extraction due to moderate to severe mandibular anterior crowding.